2018
DOI: 10.1007/s11910-018-0877-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of Brain Metastases in the New Era of Checkpoint Inhibition

Abstract: Immune checkpoint inhibitors have revolutionized the treatment of metastatic melanoma, lung cancer, kidney cancer, and bladder cancer among others. They modulate the immune system to recognize tumor antigens as "non-self" antigens and mount an immune response against them. Initial studies of using immune checkpoint inhibitors in brain metastases have shown promising activity, and several clinical trials are currently underway. Studies are also assessing the combination of radiation therapy and immunotherapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…In the 14 patients with initial CNS involvement, median OS was significantly worse (3.7 months; range 1.5-7) compared to the whole cohort (8.7 months; range 7.7-9.9) [61]. At least 16 trials investigating ICB efficacy for brain metastases are ongoing; however, none address this question in patients with mUC [62]. Whether first-or second-line ICB treats or prevents intracranial failures in mUC is currently unknown.…”
Section: Systemic Therapymentioning
confidence: 99%
“…In the 14 patients with initial CNS involvement, median OS was significantly worse (3.7 months; range 1.5-7) compared to the whole cohort (8.7 months; range 7.7-9.9) [61]. At least 16 trials investigating ICB efficacy for brain metastases are ongoing; however, none address this question in patients with mUC [62]. Whether first-or second-line ICB treats or prevents intracranial failures in mUC is currently unknown.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Several trials are ongoing to investigate the efficacy, safety, proper timing of combination of radiotherapy, and immunotherapy [62]. The results of these studies will help evaluate the status of this therapy for brain metastases.…”
Section: Combined Immunotherapy and Radiotherapymentioning
confidence: 99%
“…The immune system has its inherent immunosuppressive mechanisms or uses checkpoints to limit prolonged immune activation and inflammation, which could be detrimental to the host. 10 Tumors have co-opted these endogenous mechanisms as a means to evade immune surveillance by the host immune system. During the past decade, novel drugs targeting checkpoint pathways leading to a reinvigorated antitumor immune response have shown promising efficacy in advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, novel drugs targeting checkpoint pathways leading to a reinvigorated antitumor immune response have shown promising efficacy in advanced NSCLC. 10,11 Among immune therapies, the programmed cell death 1 (PD-1) and the programmed cell death receptor 1 (PD-L1) blockade therapies are the most investigated. Preclinical studies have demonstrated that PD-1 receptor has emerged as a dominant negative regulator of antitumor T-cell effector function when engaged by its ligand PD-L1.…”
Section: Introductionmentioning
confidence: 99%